2015
DOI: 10.3109/14397595.2015.1109578
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of abatacept in Japanese patients with rheumatoid arthritis: 104 weeks radiographic and clinical results in clinical practice

Abstract: This study suggested efficacy of abatacept treatment in Japanese patient with RA for 104 weeks in daily clinical practice. Abatacept lead to suppress joint destruction for 104 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…We observed 1-and 2-year abatacept retention rates of 77% and 53%, respectively, slightly lower than in similar studies. For example, the 1-and 2year abatacept retention rates in a 104-week study were reported to be 83.7% and 73.9%, respectively [9]. The lower retention rate in our study may have been due to our inclusion of a higher percentage of biologic-failure patients (56% vs. 38%).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…We observed 1-and 2-year abatacept retention rates of 77% and 53%, respectively, slightly lower than in similar studies. For example, the 1-and 2year abatacept retention rates in a 104-week study were reported to be 83.7% and 73.9%, respectively [9]. The lower retention rate in our study may have been due to our inclusion of a higher percentage of biologic-failure patients (56% vs. 38%).…”
Section: Discussionmentioning
confidence: 52%
“…Abatacept showed similar efficacy and safety when administered subcutaneously or intravenously, as well as low immunogenicity, in MTX-resistant Japanese RA patients [7,8]. Moreover, abatacept was shown to suppress joint destruction for 104 weeks in 92 Japanese RA patients [9], and a postmarketing surveillance (PMS) study showed that abatacept was safe and effective in Japanese RA patients [10]. In addition, some Japanese patients with established RA who attained clinical remission following abatacept treatment subsequently achieved biologic-free remission [11].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We had reported that in patients with RA, abatacept treatment achieved structural remission in small joints independent of MTX treatment. [ 29 ] Therefore, our results demonstrate that abatacept with or without MTX may suppress radiographic progressive damage of large and small joints.…”
Section: Discussionmentioning
confidence: 65%
“…Abatacept, a recombinant protein that combines the extracellular region of CTLA-4 and human IgG, has been applied as a biopharmaceutical for treating arthritis and juvenile idiopathic arthritis. Abatacept has been reported to reduce joint pain in arthritis patients for 104 weeks [18]. The affinity of CTLA-4 to its ligands, CD80 and CD86, is more than ten times higher than that of CD28, T cell co-stimulatory protein, and another receptor for CD80 and CD86 [19, 20].…”
Section: Discussionmentioning
confidence: 99%